Work accidents among the traditional fishermen community in Bunaken Coast of Sulawesi - Pissu, Reza; Doda, Diana Vanda D.; Langi, Fima Lanra Fredrik Gerald (BKM Public Health and Community Medicine, 2025)
Purpose: Work accidents are commonly experienced by workers, including fishermen. This research examines the complex factors associated with work accidents in Bunaken's fishing community. Methods: The study encompasses 63 fishermen residing in the Bunaken District, employing a total sampling method to ensure comprehensive coverage. The research provides valuable insights into the dynamics of occupational hazards faced by Bunaken's fishermen by delving into the relationship between these variables. Carefully crafted questionnaires, the investigation focuses on several key aspects, including work stress and accidents. Results: All respondents were male, middle-aged, and had worked for more than five years, with a working day lasting over 9 hours. More than half of the respondents experienced work accidents (65%) and experienced moderate-high stress (73%). The multivariate analysis confirmed that age and education were statistically significant predictors of work accidents. Conclusion: The findings are expected to contribute to the development of targeted interventions and occupational safety measures, fostering a safer and healthier working environment for the fishing community.